Numerical simulation of bolted steel connections in fire using explicit dynamic analysis - Yu, Hongxia; Burgess, I.W.; Davison, J.B.; Plank, R.J. (Journal of constructional steel research, 2008)
Behaviour of steel connections in fire is a multi-dimensional problem involving parameters such as temperature, tying forces and large deformations. Investigation of this behaviour will remain one of the main subjects for fire engineering research in the coming years. Finite element simulation plays an important role in the study of connections because fire tests are expensive to perform. Unlike normal structural analyses, finite element simulation of bolted steel connections is a challenging task, as large numbers of contacts exist in the model. This leads to convergence difficulties in static solvers. This paper explores the use of an explicit dynamic solver to analyse bolted steel connections. By comparing the results with those from static analysis and tests, it is shown that the explicit dynamic solver, with proper control, gives satisfactory predictions of the responses of steel connections up to post-failure deformations.